Exercise psychology - Buckworth, Janet; Dishman, Rod K. (Champaign, IL Human Kinetics, 2013)
Features three new chapters on exercise and cognitive function, energy and fatigue, and pain; thoroughly revised chapters on the correlates of exercise, neuroscience, stress, depression, and sleep. Includes a glossary.
Includes bibliographical references (pages 455-513) and index.
Keywords: Exercise -- Psychological aspects; Physical fitness -- Psychological aspects